A cognitive approach to urban poor housing an exploratory study of two communities in Muntinlupa City - Togonon, Larisa Glenda G. 1965- (2007)
This study seeks to find answers based on contention that the failure of current urban poor housing approaches stems from the lack of knowledge and recognition not only of the beneficiaries' housing needs and rights but, more importantly, the underlying reasons, preferences, understanding and personal knowledge of their housing environment that inform these needs...